Progress in TLE treatment from 2003 to 2023: scientific measurement and visual analysis based on CiteSpace - Cao, Zhan; Guo, Mingjie; Cao, Xun; Liu, Tiantian; Hu, Shaowen; Xiao, Yafei; Zhang, Min; Liu, Hengfang (Frontiers in Neurology, 2023)
【purpose】Temporal lobe epilepsy (TLE) is the most common cause of drug-resistant epilepsy and can be treated surgically to control seizures. In this article, we analyze the relevant research literature in the field of temporal lobe epilepsy (TLE) treatment to understand the background, hotspots and trends in TLE treatment research. 【method】We discussed the trend, frontier and hotspot of scientific output in TLE treatment research in the world in the past 20 years by searching the core collection of Web of Science. Excel and CiteSpace software were used to analyze the basic data of the literature. 【result】We identified a total of 2051 publications on TLE treatment from 75 countries between 2003 and 2023. We found that publication rate was generally increasing. The United States was the most publishing country; among the research institutions on TLE treatment, the University of California System published the most relevant literature and collaborated the most with other institutions. The co-citation of literature and keyword co-occurrence and its clustering analysis showed that the early studies focused on open surgical treatment mainly by lobectomy. In recent years, the attention of stereotactic, microsurgery and other surgical techniques gradually increased, and the burst analysis indicated that new research hotspots may appear in the future in the areas of improved surgical procedures and mechanism research.